2017
DOI: 10.1089/end.2016.0693
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Retrograde Ureteral Contrast Injection to Guide Ultrasonographic Percutaneous Renal Access in the Nondilated Collecting System

Abstract: Objectives: Ultrasound-guided percutaneous nephrolithotomy (PCNL) has become increasingly utilized. Patients with nondilated collecting systems represent a challenge: the target calix is often difficult to visualize. Here we report pilot study results for retrograde ultrasound contrast injection to aid in percutaneous renal access during ultrasound-guided PCNL. Patients and Methods: From April to July 2016, consecutive patients over the age of 18 years with nondilated collecting systems on preoperative imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Its safety for intracavitary administration has been proved by numerous clinical studies and minor adverse effects have been reported in < 0.5% of patients [20]. Chi et al first introduced CEUS to aid US-guided PCNL in five patients without hydronephrosis, via retrograde ultrasound contrast injection to improve the visibility of the collecting system, and achieved high puncture success rate up to 100% [7]. Guo and colleagues demonstrated that compared to conventional US-guided PCNL, CEUS-guided PCNL achieved higher successful rate of one puncture, shorter puncture time and lower postoperative hemoglobin loss [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its safety for intracavitary administration has been proved by numerous clinical studies and minor adverse effects have been reported in < 0.5% of patients [20]. Chi et al first introduced CEUS to aid US-guided PCNL in five patients without hydronephrosis, via retrograde ultrasound contrast injection to improve the visibility of the collecting system, and achieved high puncture success rate up to 100% [7]. Guo and colleagues demonstrated that compared to conventional US-guided PCNL, CEUS-guided PCNL achieved higher successful rate of one puncture, shorter puncture time and lower postoperative hemoglobin loss [8].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that intraoperative use of contrast-enhanced ultrasound (CEUS) in the prone position can achieve better visibility of nondilated collecting systems and facilitate more accurate puncture [7,8]. However, the puncture accuracy and safety of CEUS-guided PCNL in flank position has not been investigated so far.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the attempt of further compensation of this disadvantage, Usawachintachit et al [42] assessed the feasibility of using contrast enhanced ultrasound (CEUS), by administering a small amount of ultrasonographic contrast (Optison TM , GE Healthcare) through a retrograde placed ureteral catheter, on a pilot series of five patients with urolithiasis with indication for PCNL, but with non-dilated renal units. Puncture was successful in all cases, without side-effects related to the ultrasound contrast.…”
Section: Resultsmentioning
confidence: 99%
“…An inverted Y duplicated ureteral malformation cannot be diagnosed by clinical symptoms and is mainly diagnosed by ureterography. Retrograde ureterography routinely develops by X-rays and can also develop by contrast-enhanced ultrasound[ 8 ].…”
Section: Discussionmentioning
confidence: 99%